BRITISH STARTUP ECOSYSTEM: PROSPECTS FOR UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article outlines the unique characteristics of the startup ecosystems in both Great Britain and Ukraine. The analysis delved into the role of prominent academic institutions like Cambridge and University College London in fostering innovation and entrepreneurship. The venture funds operating in both countries, along with their areas of focus. This involved detailing the sectors they invest in (e.g., technology, biotech, fintech) and their track record in supporting startups.Based on the experience of Great Britain, the article propose strategies to boost the startup ecosystem in Ukraine.Overall, the analysis to provide a comprehensive understanding of the startup ecosystems in Great Britain and Ukraine, offering valuable insights and recommendations for enhancing the entrepreneurial landscape in Ukraine based on the experiences and successes of the UK's ecosystem.
Keywords: ecosystem, startups, Great Britain, Ukraine, venture funds, entrepreneurship, early stage of enterprise development, innovative entrepreneurship, industry, sectors